Eastern Mediterranean volcanism during marine isotope stages 9 to 7e (335-235ka): insights based on cryptotephra layers at Tenaghi Philippon, Greece - Vakhrameeva, Polina; Wulf, Sabine; Koutsodendris, Andreas; Ludwig, Thomas; Knipping, Maria; Trieloff, Mario; Pross, Jörg (Journal of volcanology and geothermal research, 2019)
Tephra layers preserved in distal sedimentary archives represent chronicles of explosive volcanism that can complement the often more fragmentary information from near-source volcanic deposits to establish complete volcanic histories. With regard to these aspects, the Middle Pleistocene of the Eastern Mediterranean region stands out as it has a complex and diverse, but as yet largely unexplored record of volcanic eruptions. Here we present the first distal tephra record for the Eastern Mediterranean region spanning from 335 to 235ka (corresponding to Marine Isotope Stages [MIS] 9 to 7e); our record has been derived from peat cores from the iconic terrestrial climate archive of Tenaghi Philippon (NE Greece). We have identified twenty-seven cryptotephra layers that represent eruptions from diverse Mediterranean sources. Six cryptotephra layers can be linked to Campanian volcanoes, and another six layers are tentatively correlated to Aeolian Arc volcanism. Of the ten cryptotephra layers that we have identified as deriving from the Aegean Arc, eight originate from Santorini volcano and two are tentatively attributed to either Kos or Milos. Five cryptotephra layers have yet unknown origins. Most of the identified cryptotephras represent previously undocumented eruptions. We provide age estimates for all cryptotephras and, by extension, for the underlying eruptions based on orbitally tuned pollen data from the same cores. The only cryptotephra layer in the 335-235ka record from Tenaghi Philippon that represents a previously known eruption has a palynostratigraphically derived age of c. 289ka and can be tentatively linked to the Seiano Ignimbrite from the Campanian Volcanic Zone; this represents the first time that this eruption can be traced beyond its proximal area. The documentation and geochemical characterization of tephra layers from different Mediterranean sources in the Tenaghi Philippon peat cores for MIS 9-7e is an important step towards the integration of regional Mediterranean tephrostratigraphic information for the Middle Pleistocene.
Gesehen am 01.08.2019